Characterisation of the nitrile biocatalytic activity of rhodococcus Rhodochrous ATCC BAA-870 - Frederick, Joni (My University, 2007)
A versatile nitrile-degrading bacterium was isolated through enrichment culturing of soil samples from Johannesburg, South Africa. It was identified as Rhodococcus rhodochrous and submitted to the ATCC culture collection as strain BAA-870. This organism was determined to be a potential biocatalyst in that it contains a two enzyme system with strong nitrile-converting activity comprising nitrile hydratase and amidase. The development of a suitable assay for measuring the activity of the enzymes of interest was explored. A pHsensitive indicator-based assay was found to be suitable only for colorimetrically identifying highly concentrated enzymes with acid-forming activity. An ophthaldialdehyde- based fluorimetric assay was found to be applicable to conversions of select compounds, but the assay could not be used to measure the activity of Rhodoccocus rhodochrous ATCC BAA-870. High performance liquid chromatography was the most suitable method for reliable and quantitative measurement of nitrile hydrolysis, and is applicable to monitoring activities of whole-cell and cell-free extracts. Initial analysis of six compounds, benzonitrile, benzamide, benzoic acid, hydrocinnamonitrile, 3-hydroxy-3- phenylpropionitrile and 3-hydroxy-3-phenylpropionic acid, was performed by HPLC to measure linearly the average retention area, amount and absorbance of the compounds up to 10 mM concentrations. The conversion of the substrates benzonitrile, benzamide and 3- hydroxy-3-phenylpropionitrile were further analysed with respect to time and enzyme concentration. Conversion of benzonitrile to benzamide by the nitrile hydratase was rapid and could be measured in 10 minutes. Conversion of benzamide to benzoic acid by the amidase was considered the rate-limiting step and could be followed for 90 minutes of the reaction at the concentrations tested. Conversion of 3-hydroxy-3-phenylpropionitrile was linearly measured over 20 minutes. Mass spectral analysis was used to confirm, at a structural level, relatively less volatile reactant compounds with a higher thermal stability, including benzamide, 3-hydroxy-3-phenylpropionitrile and 3-hydroxy-3-phenylpropionic acid. Protein concentration studies indicated that activity against benzonitrile was probably due to a nitrile hydratase with potent activity rather than a concentrated enzyme, since formation of benzamide from benzonitrile showed first order reaction kinetics at protein concentrations less than 0.2 mg/ml. Formation of benzoic acid from benzamide was linear up to 1.3 mg total protein and product formation from 3-hydroxy-3-phenylpropionitrile was linear up to 1.4 mg total protein. Overlapping activities against benzonitrile and 3- hydroxy-3-phenylpropionitrile indicate that the nitrile hydratase has differing substrate specificity for the two compounds, with higher activity toward the small aromatic mononitrile, benzonitrile, than the arylaliphatic b-hydroxy nitrile, 3-hydroxy-3- phenylpropionitrile. The nitrile-converting activity of Rhodococcus rhodochrous ATCC BAA-870 would be suitable for biocatalysis as the conversions take place under a wide pH range, require low concentrations of enzyme and reactions are fast. Separation of nitrileconverting activities in Rhodococcus rhodochrous ATCC BAA-870 was undertaken using various chromatography methods to establish a simple, one-step protocol for biocatalytic enzyme preparations. HPLC was not suited to assaying nitrile-converting activity in chromatofocusing fractions, and chromatofocusing Ampholyte buffers were found to interfere with activity measurements. Gel exclusion chromatography of the soluble protein extract from Rhodococcus rhodochrous ATCC BAA-870 indicated the enzyme/s responsible for nitrile hydratase activity are high molecular weight proteins ranging from 40 to 700 kDa in size, while the amidase native enzyme is proposed to be roughly 17 to 25 kDa. SDS-PAGE analysis of gel exclusion and ion exchange chromatography fractions indicated nitrile converting activity in Rhodococcus rhodochrous ATCC BAA-870 is likely due to multimer-forming enzymes made up of 84, 56, 48 and 21 kDa subunits. It is postulated that nitrile hydratase is made up of ab and a2b2 tetramers that may form larger enzyme aggregates. Ion exchange chromatography was used to separate nitrile hydratase with high activity against benzonitrile and 3-hydroxy-3-phenylpropionitrile from amidase activity, and showed that an additional, substrate specific nitrile hydratase may exist in the organism.
Student Number : 0009756Y - MSc dissertation - School of Molecular and Cell Biology - Faculty of Science
Keywords: biocatalyst; nitrilase; nitrile hydratase; amidase; HPLC